Penolakan Pemberian Rekomendasi Pembebanan Hak Tanggungan Terhadap Hak Guna Bangunan di atas Hak Pengelolaan Pemerintah Kalimantan Timur - Diera Ajeng Amalia (University of Udayana, 2018)
The aim of the study was to find out the misinterpretation in the East Kalimantan Government in the gubernatorial letter number: 593/5102 / BP-II / VI / 2012 concerning the reasons for refusing to provide recommendations for the guarantee of Underwriting Rights on Building Use Rights over the Government's East Kalimantan Management Rights. The research method used normative research (Statue Approach, legal concept analysis and Case Approach. The results of the study indicate the occurrence of misinterpretations in the Letter of the Governor of East Kalimantan Number: 593/5102 / BP-II / VI / 2012, in which the East Kalimantan Government as the Management Right holder refused to provide written recommendations or approval to the Building Use Rights owners, namely Housing residents Korpri Samarinda based on the provisions of Law Number 1 of 2004 concerning State Treasury in Article 49 paragraph (5) which states that